2020
DOI: 10.1097/md.0000000000019642
|View full text |Cite
|
Sign up to set email alerts
|

Motor recovery and antidepressant effects of repetitive transcranial magnetic stimulation on Parkinson disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…The H-coil has been designed to stimulate a wider area of effective cortical stimulation compared with the standard coils ( 8 ); considering the widespread cortical dysfunction in PD ( 9 ), this could be seen as a possible advantage and not as a limitation. In fact, positive results have been achieved in PD using the focal coil with sequential bilateral stimulation of M1, and possibly associating M1 and DLPFCstimulation ( 2 , 5 , 10 12 ). Moreover, an open-label pilot study performed by our group showed that high-frequency rTMS stimulation of bilateral M1 and PFC with H-coil might serve as a safe and effective treatment for PD ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The H-coil has been designed to stimulate a wider area of effective cortical stimulation compared with the standard coils ( 8 ); considering the widespread cortical dysfunction in PD ( 9 ), this could be seen as a possible advantage and not as a limitation. In fact, positive results have been achieved in PD using the focal coil with sequential bilateral stimulation of M1, and possibly associating M1 and DLPFCstimulation ( 2 , 5 , 10 12 ). Moreover, an open-label pilot study performed by our group showed that high-frequency rTMS stimulation of bilateral M1 and PFC with H-coil might serve as a safe and effective treatment for PD ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency rTMS was more effective than low-frequency rTMS. The improvement was greater under off-medication conditions (SMD 2.98) than under on-medication conditions (SMD 1.51) 15 . This is mostly in agreement with a previous 2018 meta-analysis on 23 trials, in which significant motor benefit from high-frequency M1 and SMA stimulation was reported, with greater effect from the former, while non-motor effects were demonstrated using low-frequency rTMS or stimulation over the DLPFC 16 .…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 80%
“…The motor effects of rTMS have been subjected to several meta-analyses. The most recent of these included 28 randomized controlled or crossover trials up to July 2019, with 25 trials evaluating motor symptoms in a total of 787 patients 15 . Only five rTMS studies were published subsequently, and these are discussed individually.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
See 2 more Smart Citations